2021
DOI: 10.3389/fpsyt.2021.641396
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Military Training in Improving Psychological Resilience and Reducing Depression Among College Freshmen

Abstract: Background: Military training plays an important protective role in enhancing mental health. However, the effects of military training on psychological resilience and depression among college freshmen in China remain unclear. The present study aimed to evaluate changes in psychological resilience and depression through military training among college freshmen, and to investigate associated psychosocial factors including childhood trauma that may influence its effects on psychological resilience.Methods: A pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
1
11
0
3
Order By: Relevance
“…The higher scores indicate greater ability to cope with adversity. The previous study have shown that CD-RISC has good reliability among college students [39]. In this study, the internal consistency was good, and the Cronbach's coe cients were 0.979.…”
Section: Psychological Resiliencesupporting
confidence: 55%
“…The higher scores indicate greater ability to cope with adversity. The previous study have shown that CD-RISC has good reliability among college students [39]. In this study, the internal consistency was good, and the Cronbach's coe cients were 0.979.…”
Section: Psychological Resiliencesupporting
confidence: 55%
“…In addition, this result is hardly comparable with those in the literature because different versions of the CD-RISC were used and the target population was mostly veterans. Military training includes intense mental preparation to handle extreme emotional circumstances such as war or national defense events [ 49 ]. Knowing the prevalence of resilience in this study allows us to understand that military personnel might not be adequately trained to face events such as the pandemic and provide support in different areas, such as health, transportation and security.…”
Section: Discussionmentioning
confidence: 99%
“…Each participant's psychological resilience was measured by the 10-item Connor-Davidson Resilience Scale (CDRS-10) (Campbell-Sills & Stein, 2007), a selfadministered questionnaire extracted from the original 25-item CDRS (Connor & Davidson, 2003). The Chinese version of CDRS has been validated and widely used in previous studies (Guo et al, 2021;Long et al, 2019;Ye et al, 2017). In the CDRS-10, the score of each item ranges from 0 to 4 (0 = "never" to 4 = "almost always"), and the total score ranges from 0 to 40.…”
Section: Psychological Resiliencementioning
confidence: 99%